Case Report: Rare Case of Synchronous Neck Metastasis From Metachronous Bilateral Renal Cell Carcinoma - Jun Dai; Chen Fang; Xiaoqun Yang; Xin Huang; Wei He; Chenghe Wang; Juping Zhao; Fukang Sun (Frontiers in Oncology, 2021)
Renal cell carcinoma (RCC) is a malignant tumor that can metastasize easily. Hence, many patients have already developed metastasis when they are diagnosed. It is also one of the most common tumors that metastasize to the head and neck through extranodal disease. Herein, we reported a case of a 53-year-old man with cervical metastasis from bilateral RCC. Interestingly, whole exome sequencing (WES) and clonal evolution analysis revealed that bilateral renal tumor lesions and neck metastases (squamous cell carcinoma) share the same subclones and a large number of gene variants, while the pathological morphology is different (left nephrotic foci, a mixed pattern of mucinous tubular and spindle cell carcinoma (MTSCC) with papillary adenoma; right renal foci, papillary renal cell carcinoma (PRCC)). This was first reported in RCCs to the best of our knowledge. This case suggests that genotype analysis can be a powerful supplementary examination for clinical histopathological diagnosis. Gene detection has great significance for the accurate diagnosis and treatment of RCC metastasis or multiple lesions.